Linking farm production diversity to household dietary diversity controlling market access and agricultural technology usage: evidence from Noakhali district, Bangladesh. Issue 1 (January 2022) - Kabir, Md Ruhul; Halima, Oumma; Rahman, Nahian; Ghosh, Susmita; Islam, Md. Sayedul; Rahman, Habibur
Abstract: Background and objective: Diversified agricultural production is considered a means to enhance food diversity at the household level, particularly in developing countries where subsistence farming is common. Given the importance of a diversified diet for human health and the persistent malnutrition problem in Bangladesh, a pressing issue is how different crops and livestock production affect household food diversification, and this study sought to answer that question. Methods: Using a multistage sampling procedure, data were collected from 190 small farm holder households from Hatiya (a coastal rural sub-district of Noakhali, Bangladesh). Farm production diversity (FPD) is measured using the household biodiversity index (HBI), a simple count of all crops and livestock produced on the farm. The household dietary diversity score (HDDS) is calculated, according to Food and Agriculture Organization (FAO) guidelines, by counting 12 food groups consumed by the households in the last 24 h preceding the survey. Results: On average, households consumed 6.49 food groups during the reference day, according to the household biodiversity index (HBI). The generalized Poisson log-linear regression results indicated that farm production diversity had a positive association with HDDS; one group of farm production increased the household dietary diversity (HDD) by 0.084 unit [β: 0.084, 95% CI: 0.064, 0.106; Exp (B): 1.087], an 8.7% increase in dietary diversity. Total land size, less time to reach the district market, and improved irrigation process affect dietary diversity in bivariate analysis. Farmer's reliance on production diversity reduces when the market is more accessible and improved irrigation is used for production. Conclusion: Smallholder farm households in Bangladesh could benefit from context-specific, food-based nutrition-sensitive agriculture policies that focus on triangulation of diversified production, greater market access, and updated agricultural technology utilization. Highlights: In subsistence farming, diverse agricultural production can play a vital role in ensuring diversified food consumption. In this study, a generalized Poisson regression estimator was used for modeling count data with under-dispersion. Study findings indicated that higher farm production diversity (FPD) was associated with higher dietary diversity. Farmer's reliance on FPD reduces when the market is more accessible and improved irrigation is used for production. Nutrition-sensitive agricultural practices aimed at subsistence farmers could help to achieve food diversity. Abstract : Production diversity; Household dietary diversity; Smallholder farm households; Market access; Agriculture technology; Bangladesh.